Identification of mini‐chromosome maintenance 8 as a potential prognostic marker and its effects on proliferation and apoptosis in gastric cancer. Issue 24 (6th November 2020) - Huang, Bin; Lin, Minghe; Lu, Lisha; Chen, Wujin; Tan, Jingzhuang; Zhao, Jinyan; Cao, Zhiyun; Zhu, Xiaoqin; Lin, Jiumao
Abstract: Mini‐chromosome maintenance (MCM) proteins play important roles in initiating eukaryotic genome replication. The MCM family of proteins includes several members associated with the development and progression of certain cancers. We performed online data mining to assess the expression of MCMs in gastric cancer (GC) and the correlation between their expression and survival in patients with GC. Notably, MCM8 expression was undoubtedly up‐regulated in GC, and higher expression correlated with shorter overall survival (OS) and progression‐free survival (PFS) in patients with GC. However, the role of MCM8 in GC has not been previously explored. Our in vitro experiments revealed that MCM8 knockdown inhibited cell growth and metastasis. Moreover, MCM8 knockdown induced apoptosis. Mechanistically, the expression levels of Bax and cleaved caspase‐3 were increased, whereas Bcl‐2 expression decreased. Additionally, we demonstrated that MCM8 knockdown suppressed tumorigenesis in vivo. Overall, these results suggest that MCM8 plays a significant role in GC progression.